Edukasi Parasitologi Trichomonas Vaginalis untuk Meningkatkan Kesadaran Kesehatan Reproduksi Remaja - Acivrida Mega Charisma; Yohanes Ardian Kapri Negara; Farida Anwari; Amellya Octifani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The Food & Beverage industry relies heavily on the availability and quality of fresh raw materials, making inventory management crucial. This study aims to analyze the implementation of the First-In, First-Out (FIFO) method in inventory management at PT K Hospitality Investment. The research design used a case study. Data were collected through interviews, observation, and documentation, then analyzed descriptively and qualitatively to assess the implementation of the FIFO inventory method in inventory management. The results show that PT K Hospitality Investment adopts a strict chronological inventory system and issuance of goods based on the order of entry. The use of FIFO inventory is often supported by the FEFO (First-Expired, First-Out) technique. Integrated inventory control has contributed to the financial stability of PT K Hospitality Investment. When properly implemented, the FIFO method not only helps reduce waste and increase efficiency, but also supports the company's operational sustainability. Although the implementation has been successful, the company still faces challenges such as limited infrastructure, a manual recording system, sudden changes in trends or guest order volumes, and delays in supplier deliveries.